The disappearing COVID-Naïve Population and comparative Roche vs. Abbott Test sensitivity: evidence from antibody seroprevalence in Milwaukee County, Wisconsin - Lorenzo Franchi; Vladimir Atanasov; Mark Stake; Garrett Bates; Kristen Osinski; John R Meurer; Bernard Black (Scientific Reports)
Abstract We study the prevalence of SARS-CoV-2 antibodies in a diverse population in Milwaukee County, Wisconsin from May 2021 to June 2022. We find that 99.4% (523/526) of the participants had positive results for antibodies to the SARS CoV2 spike protein over April-June 2022, soon after the early-2022 Omicron surge. Positive tests for spike protein antibodies were very high (86%; 19/22) even among unvaccinated persons who reported no knowledge of prior infection. Thus, by mid-2022, almost all persons were no longer COVID-naïve, defined as vaccination, infection (often without symptoms), or both. Nucleocapsid antibody tests, especially the Abbott test, were far less sensitive than spike protein tests, and Abbott test sensitivity faded with time since infection. Thus, studies which rely on nucleocapsid tests will understate prior infection rates. We also report large sample evidence on the performance of the Abbott and Roche spike and nucleocapsid protein tests in capturing prior vaccination, infection, or both. The Roche spike protein test outperforms the Abbott spike test, and the Roche nucleocapsid test greatly outperforms the Abbott nucleocapsid test.